APPLICATION OF CHOIR EXTRACURRICULAR ACTIVITIES TO STUDENTS' LEARNING MOTIVATION IN MUSIC ART MATERIALS AT SD NEGERI 36 BANDA ACEH - Yadi, Agusti; Fitri, Aida; Mislinawati, Mislinawati (Universitas Syiah Kuala, 2025)
This research was conducted due to students' lack of understanding of music art material and low student motivation to learn music art material. The method used to overcome this problem is through extracurricular choral activities. This research aims to determine the application of choir extracurricular activities to students' learning motivation on music arts material at SD Negeri 36 Banda Aceh. The method used in this research is qualitative with a descriptive type. The subjects in this research were 1 extracurricular music teacher and 22 students from grades 4, 5 and 6. The instruments used were observation sheets and interview sheets. The data was analyzed using data reduction, data presentation, and drawing conclusions. Based on the results of the analysis of observation activities, it is known that the learning motivation of students who take part in choir extracurriculars is at a score of 3.70 in the very good category. So it can be concluded that choir extracurricular activities have a good impact on students' learning motivation in music arts material at SD Negeri 36 Banda Aceh. So it is hoped that schools and teachers will increase their support for students to take part in extracurricular choir activities to increase students' learning motivation and develop their talents.